ANALYSIS OF THE EXPERIMENTAL AND TESTING WORK ON IMPROVING THE PROBLEM-BASED TEACHING METHODOLOGY IN GEOGRAPHY LESSONS - Jurakhujaev, Davronkhoja Daverkhoja Ugli (Journal of Geography, Regional Planning and Development, 2025)
Objective: This study investigates the effectiveness of the Problem-Based Learning (PBL) approach in enhancing geography education by fostering independent thinking, deepening theoretical knowledge, and strengthening practical skills among students. Method: A quasi-experimental design was employed, involving three stages of testing across schools in the Jizzakh, Samarkand, and Tashkent regions of Uzbekistan. Students were divided into experimental and control groups, with the experimental group taught using PBL strategies such as case studies and interactive tasks, while the control group received traditional instruction. Results: The findings reveal a 14.7% improvement in academic performance among students in the experimental group compared to the control group, demonstrating the effectiveness of the PBL approach in advancing educational outcomes. Novelty: This study provides empirical evidence supporting the integration of PBL in geography lessons within the context of Uzbekistan’s education system, offering a validated, innovative instructional model aimed at promoting analytical skills, self-directed learning, and academic achievement in secondary education.